The Effectiveness of Post-Clearance Audit: A Scoping Review - Nurwanto, Agung; Yulianti Abbas (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Customs institutions worldwide face the challenge of balancing strict border controls with trade facilitation. To address this, the World Customs Organization emphasizes the implementation of Post-Clearance Audit (PCA), a risk-based mechanism for ensuring traders’ compliance with trade regulations and protecting state revenue. This study examines existing literature on the effectiveness of PCA, following the scoping review framework by Arksey & O’Malley. Relevant studies were collected from online databases such as Scopus, ProQuest, Google Scholar and the World Customs Journal, resulting in 14 articles that met the inclusion criteria. The review reveals that while PCA has the potential to bring promising benefits, its effectiveness is often constrained by various implementation challenges. This study contributes to the understanding of PCA by highlighting key themes in the literature and offering insights for customs administrations and future researchers.